Good governance and poverty alleviation in the CEMAC sub-region: A fixed effect model with driscoll-kraay standard errors technique - Ewane, Enongene Betrand (Asian Journal of Empirical Research, 2023)
Good governance is paramount for the government of each country to reduce poverty and achieve their growth objectives. However, due to corruption, political instability, and government ineffectivesness, the quality of governance indicators has fail in most countries expecially those in the Central African Economic and Monetary Community (CEMAC). Thus, the objective of this study was to examine the effect of good governance on poverty reduction in the CEMAC sub-region using World Bank data from 1996 to 2021. Due to multicollinearity and parsimonious model, four governance indicators were examine in the study; voice and accountability (vacc), government effectiveness, corruption, and political stability while household consumption expenditure (HCE) was use as a measure of poverty allevation. The study face the problem of cross-sectional dependence and heteroscedasticity. Hence, it employs the fixed effect model with Driscoll-Kraay standard errors regression. The results indicate that vacc and government effectiveness have a positive and significant impact on poverty reduction while corruption and political stability have a negative effect. This indicates that good governance is vital in reducing poverty and boosting the livelihood of the population in CEMAC sub region. The study recommends that CEMAC member countries should step up the quality of their governance indicators such as eradication of corruption, effectiveness in governance, and adopts results based financing.